2012
DOI: 10.1136/postgradmedj-2011-130652
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of systematic reviews in a hospital setting: a comparative survey for spreading use of the Cochrane Library

Abstract: This study has identified several helpful strategies used by Taiwan's hospitals to enhance dissemination of the Cochrane Library, including raising of awareness, active delivery of information, mentoring relationships, and educational training. The data suggest that disseminating evidence-based medicine simultaneously is a key element.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…We found that not only increased usage of Internet-based resources in general, but also the trend applied to all 8 popular online EBM databases. During our study period, NHRI offered free access to the Cochrane Library to promote EBM dissemination [11,27]. Nevertheless, both physicians and nurses used a variety of databases to look for medical information rather than using the Cochrane Library alone.…”
Section: Discussionmentioning
confidence: 99%
“…We found that not only increased usage of Internet-based resources in general, but also the trend applied to all 8 popular online EBM databases. During our study period, NHRI offered free access to the Cochrane Library to promote EBM dissemination [11,27]. Nevertheless, both physicians and nurses used a variety of databases to look for medical information rather than using the Cochrane Library alone.…”
Section: Discussionmentioning
confidence: 99%
“…The Cochrane Library has been regarded as the most important resource of EBM [31]. In addition, the Cochrane Library used well-established PICO queries as a methodological standard to conduct systematic reviews [32].…”
Section: Discussionmentioning
confidence: 99%
“…EBP integrates clinical epidemiology, biostatistics, research methods, and informatics into healthcare. 1,2 The process of EBP mainly involves 4 steps: framing a clear question based on a clinical problem; finding relevant evidence in the literature; critically appraising the validity of the research; and applying the findings to clinical decision-making. 3 Respiratory care is increasingly utilized, with the associated respiratory therapists (RTs) playing an important role in supporting related clinical services.…”
Section: Introductionmentioning
confidence: 99%